Cardiac tamponade complicating leukaemia: immediate chemotherapy or pericardiocentesis?. Issue 768 (October 1989) - Leung, W. H.; Tai, Y. T.; Lau, C. P.; Wong, C. K.; Cheng, C. H.; Chan, T. K.
Abstract : Although leukaemic infiltration of the pericardium is frequently observed at post-mortem, clinically evident cardiac tamponade is rare. Two cases of cardiac tamponade complicating leukaemia are presented. One patient had cardiac tamponade as the initial presentation of acute lymphoblastic leukaemia and experienced complete resolution of the pericardial effusion within 6 days after chemotherapy without therapeutic pericardiocentesis. The other patient with chronic myeloid leukaemia developed cardiac tamponade requiring pericardiocentesis as the first sign of acute blastic transformation. The roles of early chemotherapy and pericardiocentesis in managing this complication are discussed.